Squamos cell carcinoma in the fornix of the oral vestibule - Monika Ratajek-Gruda; Jolanta Białkowska- Głowacka; Anna Janas-Naze (Kazimierz Wielki University, 2018)
The article describes a case of a long-term squamous cell carcinoma in the fornix of oral cavity. Diagnostic methods for this medical condition are also described.